A Preliminary Study on the Use of Bishop's Formula for the Prediction of Wheat Malt Extract. (7th April 2022) - Gorzelany, Józef; Belcar, Justyna
Abstract: By using Bishop's formula to assess calculated extract potential of wheat grains at the stage of wholesale purchase of the material, it could be possible to determine the quality from the viewpoint of the brewing industry. Based on this, buyers could rapidly assess the material before purchase and malt-houses could optimize the technological process. This study examined the feasibility of Bishop's formula (originally designed to identify calculated extract of malting barley) being applied to measure the calculated extract of wheat. For this purpose, ten winter cultivars of common hexaploid wheats, grown in 2019, were selected for the study. The variables applied included the cultivar and the plumpness of the wheat grains. The grains were sorted into size 2.5-2.8 mm and size > 2.8 mm for the study of nitrogen content and 1, 000 grain weight (TGW). The wheat was malted and five-day laboratory malts were obtained. The Congress mashing protocol was carried out and the actual extract of the wheat malts was determined based on the extract produced in that specific process. The actual extract values were compared to the calculated extract according to Bishop (statistical analysis). Small statistical differences were observed between the calculated and the actual extract of the wheat malts, however more research is needed to determine if Bishop's formula is as useful for wheat as it is for barley malt.